Application of molecular markers to wheat breeding in Canada. Issue 5 (28th May 2013) - Randhawa, Harpinder S.; Asif, Muhammad; Pozniak, Curtis; Clarke, John M.; Graf, Robert J.; Fox, Stephen L.; Humphreys, D. Gavin; Knox, Ron E.; DePauw, Ron M.; Singh, Asheesh K.; Cuthbert, Richard D.; Hucl, Pierre; et al.
Abstract: Marker‐assisted breeding provides an opportunity for wheat breeders to introgress/pyramid genes of interest into breeding lines and to identify genes and/or quantitative trait loci in germplasm to be used as parents. Molecular markers were deployed to assist selection for disease resistance, agronomic and quality traits in several wheat cultivars released for commercial cultivation in Canada. Marker‐assisted breeding is routinely used in most wheat breeding programmes for rust resistance (leaf, stem and stripe rust), orange wheat blossom midge resistance, high grain protein concentration, Fusarium head blight and common bunt resistance. Markers are being used selectively within breeding programmes to target traits that relate to market class or regional adaptation. For example, marker‐assisted breeding for low lipoxygenase activity and low grain cadmium is being performed in durum breeding programmes and for enhancing stem solidness in programmes targeting resistance to the wheat stem sawfly. Markers are also being utilized for ergot resistance in durum wheat. Increased gluten strength is being selected with a marker for the overexpression of the Bx7 high‐molecular‐weight glutenin subunit. Marker‐assisted breeding is also being used to pyramid resistance genes against a group of stem rust races related to TTKS (Ug99), a disease that poses a serious threat to global wheat production. Development of tightly linked diagnostic markers and high‐throughput genotyping with SNP markers will result in more effective molecular wheat breeding in the near future and will open the door to genomic selection.